A Analisis Pengendalian Piutang Pada Koperasi Pegawai Republik Indonesia (KPRI) Karya Dharma Kabupaten Tolitoli - Moh Sujai; Kiki Fatmala (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
Analysis Of Accounts Receivable Control At The Indonesian Republic Employee Cooporative (KPRI) ToliToli Regerency Dharma Works The formulation of the problem i is how the effectiveness of control of receivables in terms of the magnitude of problem loans during the last 3 years in the karya dharma tolitoli regency with the aim of knowing the effectiveness of control of receivables in the terms of the magnitude of problem loans during the last 3 years. KPRI karya dharma tolitoli regerency is located on stret Ra. Kartini number 17. This research uses descriptive quantitative data types, supported to obtain primary and secondary data that are more valid, and objective, subjects, and data were collected by observation, interview, documentation, and literature study. The analytical tool used is the ratio of protected loans to loans (RPM). Based on the results of the analysis outlined by the conclusion that in 2016 problems loans amounted to 7,40% (between 0 to 10%), in 2017 the ratio of problem loans increased by 6,70% (between 0 to 10%) and at in 2018 problem loans amounted to 8,35% (between 0 to 10%), this means that in 2016-2018 the score obtained was 4,0 with a value of 80 and included in the healthy category, bot not yet effective because of bad loans from the year 2016-2108 continues to increase